Record of hill stream catfish Glyptothorax telchitta (Hamilton-Buchanan, 1822) from Paschim Medinipur district, West Bengal, India - Arun Jana; Godhuli Sit; Angsuman Chanda (Acta Biologica Sibirica, 2021)
Glyptothorax telchitta (Hamilton-Buchanan, 1822) is a benthic hill-stream Sisoroid catfish that inhabits the mountain waters of the Indian Himalayas and in China, Tibet and the Sunda Islands. It is also a common hill stream catfish of the northern region of West Bengal. The present work reveals that the species is available in the Shilabati river basin, Ghatal, Paschim Medinipur, West Bengal. Therefore, Glyptothorax telchitta (Hamilton-Buchanan, 1822) is a widely distributed hill stream species and extends to the lowland area of Paschim Medinipur district of West Bengal, India.